(untitled) (World Bulletin of Management and Law, 2023)
From the second half of the 19th century, the territory of Turkestan was included in the plans of tsarism to seize economic space in order to meet the growing needs of Russian capitalism. For this purpose, tsarism, having disrupted traditionally developed trade relations with the Central Asian states, thanks to its superiority in military technology, began to seize the territory of Central Asia one after another. These captures took more than 20 years. A colonial regime of governance was established in the multinational region. For historical science, in the process of studying a certain era, the most important thing is the availability of historical sources. As for the immediate tsarist colonial period in the history of the peoples of Turkestan, it took exactly 50 years of rule, from the formation of the Turkestan General Government until its replacement by the Provisional bourgeois government.